High Correlation Between Structure Development and Chemical Variation During Biofilm Formation by Vibrio parahaemolyticus - Tan, Ling; Zhao, Fei; Han, Qiao; Zhao, Aijing; Malakar, Pradeep K.; Liu, Haiquan; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2018)
The complex three-dimensional structure of biofilms is supported by extracellular polymeric substances (EPS) and additional insight on chemical variations in EPS and biofilm structure development will inform strategies for control of biofilms. Vibrio parahaemolyticus VPS36 biofilm development was studied using confocal laser scanning microscopy (CLSM) and Raman spectroscopy (RM). The structural parameters of the biofilm (biovolume, mean thickness and porosity) were characterized by CLSM and the results showed that VPS36 biofilm formed dense structures after 48 h incubation. There were concurrent variations in carbohydrates and nucleic acids contents in the EPS as evidenced by RM. The Raman intensities of the chemical component in EPS, measured using Pearson’s correlation coefficient, were positively correlated with biovolume and mean thickness, and negatively correlated with porosity. The Raman intensity for carbohydrates correlated closely with mean thickness (p-value<0.01) and the Raman intensity for nucleic acid correlated closely with porosity (p-value<0.01). Additional evidence for these correlations were confirmed using scanning electron microscopic (SEM) and crystal violet staining.